HUBUNGAN PARTISIPASI MENGIKUTI KEGIATAN EKSTRAKULIKULER DAN KEDISIPLINAN BELAJAR DENGAN KEMANDIRIAN BELAJAR SISWA SEKOLAH MENENGAH ATAS NEGERI 1 BOYOLALI TAHUN AJARAN 2013/2014 - Raharjo, Ferry Fairyanto (ISSN.2252-8407)
The objective of research was to find out the significant relationship of: (1) participation in extracurricular activity to student learning independency, (2) learning discipline to student learning independency, and (3) participation in extracurricular activity and learning discipline to student learning independency in SMA Negeri 1 Boyolali in the school year of 2013/2014. This study employed a quantitative method with statistic analysis design. The population of research was all of the XI IPS (Social Science) graders of SMA Negeri I Boyolali, consisting of 66 students. The sample was taken using multistage cluster random sampling. The sample of instrument tryout was selected randomly, consisting of 16 students, so that the sample of research consisted of 50 students. Technique of collecting data used was questionnaire for X1, X2 and Y variables, while the techniques of analyzing data used were descriptive statistic and product moment correlation analyses with SPSS for windows help. Considering the result of research, it could be found that (1) the participation in extracurricular activity was related to student learning independency with rX1Y= 0.505 and ? = 0.000 so that the participation in extracurricular activity was related very significantly to the student learning independency in SMA Negeri 1 Boyolali. (2) The learning discipline was related to student learning independency with rX2Y= 0.571 and ? = 0.000 so that the learning discipline was related very significantly to the student learning independency in SMA Negeri 1 Boyolali. (3) The relationship of participation in extracurricular activity and learning discipline to student learning independency showed r X1X2Y = 0.690 and ? = 0.000, thus, the relationship participation in extracurricular activity and learning discipline to student learning independency was very significant in SMA Negeri 1 Boyolali.Keywords: Extracurricular Activity, Learning Discipline, Student Learning Independency